2023
DOI: 10.34172/ahj.2023.1441
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Relationship between Drug Addiction and Quality of Life in Herat, Afghanistan: A Cross-sectional Study

Nasar Ahmad Shayan,
Abdul Malik Hooshmand,
Ali Rahimi
et al.

Abstract: Background: Addiction is a global public health problem, with over 36 million people suffering from drug-use disorders. Afghanistan, the world’s leading opium producer, has high rates of drug use owing to the easy access to drugs in this country. This study aimed to investigate drug users’ quality of life in Herat, Afghanistan, and identify the factors affecting it. Methods: This cross-sectional study examined health-related quality of life at six rehabilitation camps in Herat, Afghanistan, from March to July … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Moreover, Iran is the most important route for transportation of opium to Europe. 3 Several studies have shown a positive association between opium use and the risk of respiratory diseases as well as laryngeal, esophagus, bladder, pancreatic, and stomach cancers. [4][5][6][7] In addition, devastating effects of long-term consumption of opium would be associated with defects in mesocorticolimbic dopamine system functions leading to some behavioral and serious psychological abnormalities.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Iran is the most important route for transportation of opium to Europe. 3 Several studies have shown a positive association between opium use and the risk of respiratory diseases as well as laryngeal, esophagus, bladder, pancreatic, and stomach cancers. [4][5][6][7] In addition, devastating effects of long-term consumption of opium would be associated with defects in mesocorticolimbic dopamine system functions leading to some behavioral and serious psychological abnormalities.…”
Section: Introductionmentioning
confidence: 99%